An analysis of the performance characteristics of world-class male speed skaters in the 500m race estimating the propulsive force per section - Yokozawa, T.; Kimura, Y.; Saikawa, F.; Kato, T.; Kumagawa, D. (Journal of High Performance Sport, 2022)
This study aimed to investigate the average speed, estimated propulsive force, and excess distance in each section of the 500m race for men at a senior international competition and to assess the race patterns of world-class speed skaters. The motion of the top 12 speed skaters who started in the inner and outer lanes (IL and OL), respectively (n=24), was captured at 60 frames/s using a local position measurement system that automatically identifies the skaters` trajectory and speed. The 500m lane was divided into six sections, and the average speed in each section was calculated. Additionally, the propulsive force for each section was estimated by the change in the speed and assumed magnitude of the air resistance during the corresponding section. The excess distance in the curved sections was calculated as the difference between the actual skating distance and official lane distance. As a result, for both the IL and OL, the skaters with an overall greater average speed had a greater average speed from the crossing straight to the second curved section and a greater estimated propulsive force to the first curved section. Among the excellent skaters, sections for which estimated propulsive forces were larger differed depending on the skater in both the IL and OL. Skaters with a higher official record for the IL had a smaller excess distance. Our observations suggest that the higher average speed in a particular section could be attributed to the larger propulsive force in the previous section, and the propulsive force to the first curved section was important for the 500m race for men.